A need to heal: an autoethnographic bildungsroman through the shadows - Culkin, David T. (Kansas State University, 2016)
How can an adult make meaning from and develop through experiences of mental illness, spiritual awareness, and death? The purpose of this autoethnographic bildungsroman is to explore how a male in the general population describes how life events have influenced his identity development over a period of 23 years, spanning three decades. The researcher-participant asks two primary questions: 1) How does the individual describe his adult development in terms of life events or “individual and cultural episodes” (Smith & Taylor, 2010, p. 52) related to mental illness, spiritual awareness, and death over time? and 2) How does the individual describe his possible selves in constructing a new sense of identity? Addressing these questions contributes to the literature of adult and continuing education by providing a glimpse into stories of lived experiences over time in the light of adult development.
Keywords: Autoethnography; Identity development; Shadows; Mental illness; Life events; Possible selves